Genetically engineered cell membrane-coated nanoparticles for antibacterial and immunoregulatory dual-function treatment of ligature-induced periodontitis - Deng, Yangjia; Ren, Mingxing; He, Ping; Liu, Fengyi; Wang, Xu; Zhou, Chongjing; Li, Yuzhou; Yang, Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
Periodontitis is an immune disease caused by bacterial infection and maintains a high prevalence worldwide. However, conventional pharmacological treatments still present the challenge of not effectively synergizing antimicrobial and immunomodulation. Inspired by the critical role of toll-like receptor 4 (TLR4) in bacterial recognition and immune activation, this paper demonstrated a combined antibacterial-immunoregulatory strategy based on biomimetic nanoparticles. TLR4-expressing cell membranes by genetic engineering and silk fibroin nanoparticles (SNs) loaded with minocycline hydrochloride (Mino) were used to prepare a biomimetic nanoparticle (MSNCs) with both antibacterial and immunoregulatory capabilities. In vitro studies had shown that MSNCs effectively targeted bacteria via TLR4 and acted as molecular decoys to competitively neutralize lipopolysaccharide (LPS) in the microenvironment as well as inhibit inflammatory activation of macrophages. In vivo, MSNCs effectively attenuated periodontal tissue inflammation and alveolar bone loss in a ligature-induced periodontitis (LIP) mouse model. In conclusion, MSNCs provide a new and effective strategy for the treatment of periodontitis and have good potential for application in various types of pathogenic bacterial infections.